The Implementation of Problem-Based Learning (PBL) Model to Improve Students' Learning Outcomes and Critical Thinking Skills in Social Studies-Geography at SMP Negeri 77 Maluku Tengah - Lalopua, Sanny Frince; Pinoa, Wiclif Sepnath (GEOFORUM, 2025)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) model in improving students' learning outcomes and critical thinking skills in the Social Studies-Geography subject at SMP Negeri 77 Maluku Tengah. The research approach used is Classroom Action Research (CAR) with two cycles. Each cycle consists of planning, action, observation, and reflection stages. The research subjects were 13 eighth-grade students. Data were collected through learning outcome tests, student activity observations, and teacher interviews. The results showed that the implementation of the PBL model increased students' active engagement in learning, improved conceptual understanding, and developed critical thinking skills. In the first cycle, most students still had difficulty analyzing the given problems, while in the second cycle, there was a significant improvement in problem-solving, argumentation, and conceptual understanding. The average student score increased from 70.37% in the first cycle to 83.84% in the second cycle. In conclusion, the PBL learning model is proven to be effective.